Boosting African exports by exchange rate? - (:unkn) unknown (My University, 2025)
Exports play a fundamental role in the diversification of goods produced and the sectoral development of Africa. Due to the intensity of the global competition, boosting exports remains a major challenge. This article examines how real exchange rate undervaluation can provide a competitive advantage to achieve this goal. Covering 41 African countries between 1995 and 2017, it analyzes growth accelerations (surges) and their econometric determinants among149 primary and manufactured products (four-digit Harmonized System, HS4). Among these observations, 96 episodes of export surges are identified.
Keywords: African Research